Profit, not health, driving Europe's Syria agenda - Marc Johan Botenga (Social Medicine Publication Group, 2014)
The Syrian conflict has cost over 130,000 lives, and forced over 7 million people, nearly a third of the total population, to flee their homes. Through arms deliveries, unbalanced diplomatic efforts, and unwavering support for Qatari and Saudi-Arabian interventions in the conflict, both the US and Europe have contributed in no small part to the escalation of the conflict. Far less known is how the European Union's pre-conflict health advocacy in Syria likely facilitated the current radicalization by widening the gap between the people and a state basing much of its legitimacy on the provision of social services.